Value based management - Martin, John D. (Harvard Business School Press, 2000)
Why do some firms create extraordinary value for shareholders, while others destroy it? A powerful suite of value based management tools can make the difference. Value based management (VBM) refers to tools that financial managers can use to plan, monitor, and control a firm's operations in ways that enhance shareholder value...